Evaluating User Experience of OpenProject at PT Promanufacture Indonesia Salatiga using the User Experience Questionnaire (UEQ) Method - Adventien, Irene Puspa; Maria (SCOPUS ID: 57093633500), Evi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The purpose of this study is to evaluate the user experience of OpenProject at PT Promanufacture Indonesia Salatiga using the User Experience Questionnaire (UEQ) method. The UEQ method was chosen for its effectiveness in measuring user satisfaction and analyzing the quality of user experience across six main evaluation scales: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. Data were collected from 100 OpenProject users at PT Promanufacture Indonesia Salatiga and analyzed based on the average scores for each scale category. The results showed that most categories received positive ratings, with average scores above 0.8, except for the attractiveness scale, which fell into the